Kelekatan Anak dengan Pengasuh Tempat Penitipan Anak - Heni Puspita (PG-PAUD Trunojoyo, 2019)
This article aims to describe the relationship between a child who is cared for in a Child Care Center and a caregiver. This study used a qualitative approach with phenomenological research methods with the subjects of the study as many as 2 caregivers in the Yasmin Jember Daycare and 6 children who were cared for with criteria for pure daycare for children and school landfill children. Child Care Center is a form of Early Childhood Education institution that functions to be a substitute carer for families with learning programs that place more emphasis on children's life skills according to the age stage. As a family substitute institution in parenting, it is common practice to form a pattern of attachment to the relationship between a child and a caregiver. Caregivers act as a substitute for parents having duties and functions to stimulate aspects of child development. In a relationship like this there is a form of acceptance or rejection that affects the closeness of the child to the caregiver.